New technologies and human rights : challenges to regulation - Cunha, Mario Viola de Azevedo (Ashgate, 2013)
The contributors to this book explore the political discourse and power relations of technological growth and human rights issues between the Global South and the Global North and uncover the different perspectives of both regions. They investigate the conflict between technology and human rights and the perpetuation of inequality and subjection of the South to the North. With emerging economies such as Brazil playing a major role in trade, investment and financial law, this book examines how human rights are affected in Southern countries and identifies significant challenges to reform in the.